Peran Penggunaan Social Media Management Pada UMKM Kripik Pisang “Cau Gelis” Berdasarkan Perspektif Community Engagement (Studi Kasus pada Kripik Pisang Cau Gelis di Kembangan) - Ridwan, Muhammad Dzaki; Shiratina, Aldina (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
The "Cau Gelis" Banana Chips Micro, Small, and Medium Enterprise (MSME) faced growth challenges due to conventional marketing and the absence of structured operational management. To address this, a social media management project was implemented using the Social Commerce System method, which integrates the Instagram and TikTok platforms to create a unified transaction flow. This article analyzes the project's outcomes from the perspective of the strategic role of community engagement, encompassing partner interaction, social media financial management, crisis management, and online reputation. The implementation yielded significant impacts, evidenced by an increase in monthly net profit from IDR 3,616,000 to IDR 5,899,000 and a Return on Investment (ROI) reaching up to 47.8. From a community engagement perspective, this success was driven by strong partner collaboration and effective reputation crisis handling. This project proves that the application of a Social Commerce System, when evaluated through the lens of community engagement, is an effective strategy for improving financial performance and building a strong digital foundation for MSMEs.